Protic Ionic Liquids Based on Anionic Clusters ([Hmim][(Hso4)(H2so4]X) with (X = 0 1 and 2 to Produce Nanocellulose (Cnc) - Ruiz-Leon, D; Ruiz-Leon, D (Elsevier B.V., 2022)
This work deals with the production of crystalline nanocellulose (CNC) through an acid hydrolysis reaction using protic ionic liquids (PILs) as solvents and catalysts. The PILs used belong to a series derived from a common cation, 1-methyl- imidazolium and anionic clusters of the general formula [(HSO4)(H2SO4)x]− (x = 0, 1, 2). These PILs were used for the first time to obtain CNC from two commercial cellulose samples and one cellulose from a corn husk source. The PILs were used under different time and temperature conditions to set the optimal parameters for extraction. The CNCs obtained were characterized by IR spectroscopy, X-ray diffraction spectroscopy, STEM and FESEM microscopy and thermal stability by thermogravimetric analysis (TGA). It was determined that the [Hmim][(HSO4)(H2SO4)x] with x = 1 presents the appropriate acidity, (measured by Hammett acidity function (H0) and acceptor number (AN) parameters), to extract CNC from two different commercial cellulose with a yield of ca 73 % and 60% (at 40 °C with 2–3 h of reaction); respectively. The experimental conditions used in this study (time and 40 °C) are milder than those reported when sulfuric acid and other ILs were used to obtain CNC. The [Hmim][(HSO4)(H2SO4)x] with x = 1 present an adequate acidity for the selective water-insoluble oligosaccharides release, while products resulting from 64% sulfuric acid (H0 = 0.65) at 40 °C were mainly water-soluble oligosaccharides. Additionally, the PILs were recycled 5 times maintaining their original structural and catalytic properties. The proposed process was also compared with a conventional acid hydrolysis using sulfuric acid (64 wt%), the nanomaterial obtained with the PILs always presented better thermal properties. This work contributes towards the use of new solvents-catalysts in the field of biomass waste recovery under mild reaction conditions. © 2022 Elsevier B.V.